Trypophobia an Unrevealed Truth: A Glance of Its Awareness and Prevalence in General Population of Pakistan - Gul, Somia; Aziz, Aisha; Jilani, Afsa (Bangladesh Journal of Medical Science, 2023)
Background: Trypophobia is a psychological fear and has been described as a phobia to images with high-contrast energy at low and midrange spatial frequencies, such as holes and repetitive patterns. Method: This randomized study was conducted from September 2016 to March 2017 (n=214) through online surveys, visiting various university departments, interviewing common laymen and individuals from dissimilar families to approach maximum number of participants with less biasness. This was a useful survey for assessing the level of awareness and number of causalities in Pakistani population. Result: Results of current study show that there were few individuals diagnosed with trypophobia and were trying to get rid of it. Other individuals were either unknown or confused about this fear. Conclusion: We conclude that this study is beneficial for assessing presence of trypophobic fear in Pakistani population. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 638-642